The Underestimated Compression Effect of Neoprene Wetsuit on Divers Hydromineral Homeostasis - Castagna, O.; Blatteau, J.-E.; Vallee, N.; Schmid, B.; Regnard, J. (International Journal of Sports Medicine, 2013)
This study aimed at demonstrating that the neoprene wetsuit provides not only thermal protection. Compression it exerts on the diver’s shell significantly impacts hydromineral homeostasis by restraining the systemic vascular capacity and secondarily increasing urine output on dry land and during scuba diving. 8 healthy divers underwent five 2-h sessions: sitting out of water in trunks (control situation), sitting out of water wearing a wetsuit, and 3 wetsuit scuba-immersed sessions at 1, 6 and 12 msw depth, respectively. Urine volumes and blood samples were collected. Hemoglobin (Hb), hematocrit (Ht) and plasma sodium concentration were measured. Interface pressure between the garment and the skin was measured at 17 sites of the body shell, with a pressure transducer. Mean interface pressures between wetsuit and skin amounted to: 25.8±2.8 mm Hg. Whatever the depth, elastic recoil tension of wetsuit material was unchanged by immersion. Weight loss was respectively 2 and 3 times greater when wetsuit was worn out of water (430 g) and during immersion (710 g) than when divers did not wear any wetsuit out of water (235 g; p<0.05). Urine volume accounted for 85% of weight loss in either session. Weight loss and urine volume were similar whatever immersion depth. The decrease in plasma volume amounted to 8% of urine volume when divers did not wear any wetsuit out of water, and to 30% when wetsuit was worn out of water or during immersion. Diving wetsuit develops a pressure effect that alters diver’s hydromineral homeostasis. During immersion, the wetsuit pressure merges into the larger main effect of hydrostatic pressure to reduce water content of body fluids, unrelated to immersion depth.
Keywords: diving wetsuit; body compression; fluid balance; urine output; plasma volume